Aesthetics of Religion : a Connective Concept. - Grieser, Alexandra K. (Religion and reason., 2017)
Sinceits founding by Jacques Waardenburg in 1971, Religion and Reason has been a leading forum for contributions on theories, theoretical issues and agendas related to the phenomenon and the study of religion. Topics include (among others) category formation, comparison, ethnophilosophy, hermeneutics, methodology, myth, phenomenology, philosophy of science, scientific atheism, structuralism, and theories of religion. From time to time the series publishes volumes that map the state of the art and the history of the discipline.